Emergency Medicine Gender in Resident Leadership Study (EM GIRLS): The Gender Distribution Among Chief Residents - Mannix, Alexandra (AEM Educ Train, 2020)
OBJECTIVES: The goal of this research was to determine the gender distribution of chief residents in emergency medicine (EM) residencies in the United States to explore whether the gender leadership gap is present at the resident level in EM. METHODS: The investigators compiled a list of EM residency programs accredited by the Accreditation Council for Graduate Medical Education. Investigators reached out to the programs using established best practices in survey distribution collecting the following: program name, program location, program length, total number of residents, total number of female residents, total number of chief residents, and the total number of female chief residents. RESULTS: Of the 223 programs contacted 194 programs responded and 182 programs were included in the study (a response rate of 82%). As of the 2019 to 2020 academic year, female EM residents account for 37.0% (2,459/6,718) of all EM residents and female EM chief residents account for 42.2% (250/593) of EM chief residents. The proportion of female EM chief residents was significantly higher than the proportion of both female EM residents (42.2% vs. 37%, p = 0.007) and female EM attending physicians (42.2% vs. 27.5%, p < 0.001). When comparing proportions of female residents based on duration of program, female physicians comprised 35.0% (1,652/4,720) of residents at 3‐year programs and 40.4% (807/1998) of residents at 4‐year programs (p < 0.01). CONCLUSIONS: While the proportion of female EM residents remains significantly lower than the proportion of male residents, females and males are similarly represented at the chief resident role.